As propriedades espectroscópicas, fotoquímicas, fotofísicas e eletroquímicas do complexo de Ru(II) cis-[Ru(tbbpy)2(4Apy)2]2+, em que tbbpy = 4,4’-ditert-butil-2,2’-bipiridina e 4Apy = 4-Aminopiridina - Rezende, Daniel Victor Alves (Universidade Federal de São Carlos, 2021)
This work involves the synthesis and characterization of the cis-[Ru(tbbpy)2(4Apy)2]2+ complex where tbbpy = 4,4'-di-tert-butyl-2,2'-bipyridine and 4Apy = 4-Aminopyridine, determination of spectroscopic, photochemical and photophysical properties. The characterization by elementary analysis measures (C,H,N) confirmed the minimum proposed formula (theoretical: %C 49.51; %H 5.42; %N 10.04; experimental: %C 49.20; %H 5.95; %N 9.80). The cis-[Ru(tbbpy)2(4Apy)2] 2+ geometry was obtained by hydrogen nuclear magnetic resonance (1H NMR) measurements. The complex presents intense absorption in the UV region with maximum wavelength at 246 nm (E = 3.54x104 mol-1cm-1L), 294 nm (E= 6.11x104 mol-1cm-1L), 332 nm (E = 1.54x104 mol-1cm-1L) and intense absorption in the visible with maximum at 490 nm (E= 9.31x103 mol-1cm-1L). The emission spectrum in CH3CN has a maximum at 658 nm which is independent of the excitation wavelength. The cyclic voltamogram shows a redox pair at 1.08 V and 0.98 V, referring to the oxidation process and reduction of ruthenium. The complex is stable in the solid state and slightly soluble in aqueous medium (pH 2 to 8). The irradiation with continuous light of 450 and 518 nm resulted in the dissociation of the two 4Apy in aqueous medium and in organic solvents and in the suppression of the emission of the complex. The comparison of computational calculations with the experimental data obtained contributed relevantly to the understanding of the photochemical and photophysical properties of the cis-[Ru(tbbpy)2(4Apy)2]2+ complex, observing a satisfactory similarity and compatible information regarding the triplet state of lower energy responsible for the emission, in which it comes from an electronic 3MLCT transition, presenting an E0-0 of 660 nm, similar to the experimental emission observed at 658 nm.
The spectroscopic, photochemical, photophysical and electrochemical properties of the Ru(II) cis-[Ru(tbbpy)2(4Apy)2]2+, where tbbpy = 4,4'-ditert-butil-2,2'-bipyridine and 4Apy = 4-Aminopyridine
Keywords: Fotoquímica; Síntese e caracterização de complexo; 4-Aminopiridina; Propriedades espectroscópicas; Complexo de Rutênio; Photochemistry; Synthesis and characterization of complex; 4-Aminopyridine; Spectroscopic properties; Ruthenium Complex; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FOTO-QUIMICA INORGANICA